Sifat permesinan kayu kumpang (Albizia sp.), khususnya kehalusan [Machining properties of kumpang wood (Albizia sp.), in particular wood surface smoothness, at two different moisture content] - Achmad Supriyadi; Esti Rini Satiti (Kementerian Perindustrian, 2021)
This manuscript presents the research on the machining properties of kumpang (Albizia sp.) wood, in particular wood surface smoothnes, which were tested at two moisture contents, 14% and 10 %, respectively. Machining properties was tested according to the modified ASTM D-1666-64 standard method. The machining properties observed were planing, shaping, boring, turning and sanding. The number of replications for each observation variable was five, so the total sampel test was fifty pieces. Visual observation was performed using loupe at 10x magnification. The results showed that kumpang wood with 10% moisture content had a higher values of defect-free machining properties than of wood with 14% moisture content. However, the moisture content significantly influenced only on boring and turning properties, whereas the properties of planing, shaping and sanding were not significantly different. Quality of planing, shaping and turning was good, while boring and sanding was very good. Kumpang wood could be recommended for processed wood products due to its good to very good machining properties.